De la Béatrice française de Berlioz à la Béatrice allemande de Richard Pohl : traductions interlinguistique et intersémiotique - Loriot, Charlotte (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Inspired by Much Ado about Nothing of Shakespeare, the comic opera Béatrice et Bénédict of Berlioz countains a significant amount of irony. Richard Pohl, the author of the German translation, removed several strokes of irony for the performances in Weimar in 1863. This choice shows linguistic and cultural obstacles, as well as a specific aesthetic and ideological orientation. Irony, moreover, contributes to the different semiosis used in opera and circulates between text, music and theater. Music remains the same in both versions, but the new text changes the general atmosphere.